(untitled) (Gestão & Regionalidade, 2022)
The objective this paper is to analyze the degree of organizational innovation of the ceramic industries in the city of Itajá/RN. The research was configured as an exploratory and descriptive approach, in which, through semi-structured interviews with the managers of eight companies in the segment, these were analyzed for the thirteen dimensions of the Innovation Radar. The obtained results point to the inexistence of the accomplishment of great innovations in these companies in the last years; the measures adopted are punctual and not systematic, aiming only at the correction and optimization of some administrative and operational functions. Despite this, the conclusions indicate that it is possible to verify how much the ceramic industries are applying some actions necessary to remain competitive in the market, through the few measures implemented by each of them.